The practical OPNET user guide for computer network simulation - Sethi, Adarshpal S. (CRC Press, 2013)
"This book provides a practical, hands-on reference for the most widely used computer network simulation software: OPNET. It explains how to use OPNET software packages for simulation and modeling of computer networks. The authors also provide a collection of laboratory projects, focusing on the most common simulation and modeling tasks performed by computer networking systems professionals and students who use OPNET software. The introductory labs demonstrate how to set up simulations, run them, and analyze results. More advanced labs address the simulation of networking protocols in various protocol layers and for wireless and mobile networks"--